Simultaneous Determination of Cobalt(II) and Nickel(II) by Fourth-Order Derivative Spectrophotometric Method Using 2-Hydroxy-3-Methoxy Benzaldehyde Thiosemicarbazone. (4th July 2007) - Kumar, A. Praveen; Reddy, P. Raveendra; Reddy, V. Krishna
Abstract : A simple and new simultaneous fourth derivative spectrophotometric method is proposed for the analysis of a two-component system containing cobalt(II) and nickel(II) without separation using 2-hydroxy-3-methoxy benzaldehyde thiosemicarbazone (HMBATSC) as a chromophoric reagent. The reagent reacts with cobalt(II) and nickel(II) at pH 6.0, forming soluble brown and yellow colored species, respectively. Cobalt(II) and nickel(II) present in the mixture are simultaneously determined without solving the simultaneous equations by measuring the fourth derivative amplitudes at 468.5 nm and 474.5 nm, respectively. The derivative amplitudes obey Beer's law at 468.5 nm and 474.5 nm for Co(II) and Ni(II) in the range 0.059–3.299 μ gmL - 1 and 0.058–3.285 μ g mL - 1, respectively. A large number of foreign ions do not interfere in the present method. The present simultaneous method is used for the determination of micro amounts of cobalt in biological samples, nickel in plant samples, and in some alloy steels and soil sample.